2023
DOI: 10.1002/jmri.28706
|View full text |Cite
|
Sign up to set email alerts
|

A Graph Theory Study of Resting‐State Functional MRI Connectivity in Children With Carbon Monoxide Poisoning

Abstract: BackgroundThe effect of carbon monoxide (CO) poisoning on the topology of brain functional networks is unclear, especially in children whose brains are still developing.PurposeTo investigate the topological alterations of the whole‐brain functional connectome in children with CO poisoning and characterize its relationship with disease severity.Study TypeCross‐sectional and prospective study.SubjectsA total of 26 patients with CO poisoning and 26 healthy controls.Field Strength/SequenceA 3.0 T MRI system/echo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…In this issue of JMRI , Liu et al 6 reported on the resting‐state functional connectivity alterations in children with CO intoxication. The main purpose of the study was to investigate the topological alterations of the whole‐brain connectome in children with CO intoxication and correlate the graph theory measures with disease severity.…”
mentioning
confidence: 99%
“…In this issue of JMRI , Liu et al 6 reported on the resting‐state functional connectivity alterations in children with CO intoxication. The main purpose of the study was to investigate the topological alterations of the whole‐brain connectome in children with CO intoxication and correlate the graph theory measures with disease severity.…”
mentioning
confidence: 99%